Incidence and Impact of Reported Infectious Endophthalmitis Events Following Cataract Surgery in Pennsylvania Ambulatory Surgery Centers - Lynette Hathaway; Shawn Kepner; Rebecca Jones (Patient Safety, 2019)
Infectious endophthalmitis is a severe eye infection that can occur following cataract surgery. In this study, we sought to explore post-cataract infectious endophthalmitis events reported by ambulatory sur-gery centers (ASCs) in Pennsylvania. We queried the Pennsylvania Patient Safety Reporting System (PA-PSRS) database for post-cataract endophthalmitis events that occurred be-tween 2009 and 2018. In the 10 cal-endar years analyzed, we identified 174 reports of post-cata-ract endophthalmitis, with rates per 1000 cataract procedures anging from 0.05 in 2009 to 0.19 in 2018. The vast majority of these events were classified as serious (93%; n = 162 of 174), reflecting harm to patients, with one resulting in enucleation (the need to remove the affected eye). Healthcare staff and all involved stakeholders should act now by identifying sources of potential perioperative contamination, adhering to evidence-based infection prevention practices, and prioritizing areas of opportunity for improvement.